Impacts of coaching, empowerment, and social capital from managers on employees’ commitment to the organization: Moderating effect of co-workers’ supports - Le, Xuan Quynh Anh; Nguyen, Thi Thuy; Bui, Thi Nhi; Tran, The Nam; Pham, Nguyen Huyen Tran (Journal of Finance - Marketing Research, 2022)
The commitment of employees with organization is a critical issue for any managers. This study is conducted to verify the impacts of leaders on employees’ commitment, especially three factors: coaching; empowerment; social capital. Furthermore, the moderating effect of co-worker supports is also examined. The mixed research method which included qualitative method and quantitative method is used. The primary data of 196 respondents who work in banks in Ho Chi Minh city as middle managers was analyzed with PLS-SEM method through the software SmartPLS. All three hypotheses about the impacts of independent variables on employees’ commitment are accepted, but three hypotheses about the moderating effect of “co-workers’ support” are rejected. In theory, the research results consolidated the prediction of social exchange theory that when employees received more favor from managers, they will engage more with the organization. In practice, the concerns and sharing of leaders with employees is a good tool to increase employees' commitment to the organization